The Influence of Teacher Teaching and Guidance of Parents on Student Achievement with Mediation of Learning Motivation in Santo Yoseph Denpasar - Ida Ayu Sasmitha Putri; Putu Ngurah Suyatna Yasa; Ni Luh Anik Puspa Ningsih (Jurnal Ekonomi dan Bisnis Jagaditha, 2020)
The study aims to determine the influence of teacher teaching methods on student achievement, the influence of teacher teaching methods on the motivation of Learning, the influence of parental guidance on the motivation of Learning, the influence of parental guidance on student achievement, the influence of motivation to learn to students ' achievements, how the motivation to learn to influence teacher teaching methods on student achievement. This study was conducted on the SMAK of Santo Yoseph Denpasar. In this research student achievement is influenced by teacher teaching methods, parental guidance and motivational learning. The respondent in this study was 120 students of SMAK Santo Yoseph Denpasar. Data analysis is done using PLS (partial least square). The results showed that teacher teaching methods are positively and significantly impactful to student achievement. Then, teacher teaching methods have positive and significant influence on student achievement, proven. Furthermore, parental guidance positively and insignificant towards learning motivation, on student achievement, not proven. Learning motivation positive and significant impact on student achievement. The motivation to learn to process the relationship between teacher teaching methods to student achievement, is not proven. The motivation to learn to publish the relationship between parents ' guidance on student achievement, proven.